Effect of iron endpoint during Peirce-Smith converting on matte mineralogy and downstream processing of base and platinum-group metals - Thyse, Elton Llyle (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD) -- Stellenbosch University, 2014.